Monty Python's Life of Brian [videorecording (Blu-Ray)] - Chapman, Graham, 1941-1989; Cleese, John; Gilliam, Terry (Criterion Collection, 2026)
The anarchic irreverence of British comedy legends Monty Python is at its most inspired in this brilliant send-up of the blockbuster biblical epic. In a stable in ancient Jerusalem, a child is born a child who will grow up to be Brian, an ordinary Judean who goes on to live an extraordinary life, becoming entangled in a plot to overthrow the Roman empire and being mistaken for the Messiah, among other unlikely events. Featuring ribald Roman puns, sharp political commentary, and an audacious crucifixion-themed musical number, the Pythons' most ambitious film is a hilarious satire of dogma and blind faith in which nothing is sacred.